Patient exposure dose in interventional cardiology per clinical and technical complexity levels. Part 1: results of the VERIDIC project. (January 2023) - Feghali, Joelle Ann; Delépierre, Julie; Belac, Olivera Ciraj; Dabin, Jérémie; Deleu, Marine; De Monte, Francesca; Dobric, Milan; Gallagher, Aoife; Hadid-Beurrier, Lama; Henry, Patrick; Hršak, Hrvoje; Kiernan, Tom; et al.
Background: Patients can be exposed to high skin doses during complex interventional cardiology (IC) procedures. Purpose: To identify which clinical and technical parameters affect patient exposure and peak skin dose (PSD) and to establish dose reference levels (DRL) per clinical complexity level in IC procedures. Material and Methods: Validation and Estimation of Radiation skin Dose in Interventional Cardiology (VERIDIC) project analyzed prospectively collected patient data from eight European countries and 12 hospitals where percutaneous coronary intervention (PCI), chronic total occlusion PCI (CTO), and transcatheter aortic valve implantation (TAVI) procedures were performed. A total of 62 clinical complexity parameters and 31 technical parameters were collected, univariate regressions were performed to identify those parameters affecting patient exposure and define DRL accordingly. Results: Patient exposure as well as clinical and technical parameters were collected for a total of 534 PCI, 219 CTO, and 209 TAVI. For PCI procedures, body mass index (BMI), number of stents ≥2, and total stent length >28 mm were the most prominent clinical parameters, which increased the PSD value. For CTO, these were total stent length >57 mm, BMI, and previous anterograde or retrograde technique that failed in the same session. For TAVI, these were male sex, BMI, and number of diseased vessels. DRL values for Kerma-area product ( P KA ), air kerma at patient entrance reference point ( Ka, r ), fluoroscopy time (FT), and PSD were stratified, respectively, for 14 clinical parameters in PCI, 10 in CTO, and four in TAVI. Conclusion: Prior knowledge of the key factors influencing the PSD will help optimize patient radiation protection in IC.